MENGANALISA MODEL PEMBELAJARAN DARING KONSEP GETARAN DAN GELOMBANG UNTUK SISWA SMK DI MASA PANDEMI COVID-19 - Agung Rahmadi (JURNAL PEMBELAJARAN FISIKA, 2021)
The COVID-19 pandemic that has hit the world has forced governments to take various measures to suppress the transmission of the virus. One of the efforts made by the government in the education sector is learning that is carried out without face to face or done online. This online learning model is a policy issued by the government for the sustainability of learning at all levels of education. SMK as an educational institution that creates work-ready graduates so that it demands a learning model that is able to develop the concept of student skills. In physics learning, especially related to vibrations and waves which are still considered difficult for students. This study aims to analyze the online learning model of the concept of vibration and waves in vocational students during the Covid 19 pandemic. This study uses a qualitative descriptive with the type of library research, where data is collected based on the results of a literature review such as books, journals, magazines, and articles. The results of the study show that the online learning model that is applied still has various kinds of obstacles in the process, especially on vibration and wave material for vocational students who need a learning media to be able to hone their skills. Key word : Covid 19 Pandemic, e-learning model, SMK